Physical activity in metabolic syndrome - Chomiuk, Tomasz; Niezgoda, Natalia; Mamcarz, Artur; Śliż, Daniel (Frontiers in Physiology, 2024)
Obesity has become one of the global epidemics, contributing to the burden of disease in society, increasing the risk of diabetes, cardiovascular and liver diseases. Inadequate energy balance resulting from excessive energy intake and insufficient physical activity (PA) is one of the main factors contributing to the incidence of obesity and the development of metabolic syndrome (MetS). Treatment options for obesity include lifestyle modifications, pharmacotherapy and bariatric surgery, with the latter being the most effective treatment. Lifestyle interventions involving increased PA and reduced caloric intake improve metabolic outcomes. Early implementation of exercise leads to improved physical fitness, better glycemic control and lipid profile. Undertaking systematic PA is associated with better quality of life, improves insulin sensitivity, causes additional weight loss, reduces its adverse effects on bone mass and results in better body composition. In this narrative review we summarized the current state of knowledge on the impact of PA on the components of MetS and the latest recommendations for PA in patients with MetS.